Reduced 11beta-hydroxysteroid dehydrogenase type 1 activity in obese boys. - Wiegand, S; Richardt, A; Remer, T; Wudy, SA; Tomlinson, J; Hughes, B; Grüters, A; Stewart, P; Strasburger, C; Quinkler, M (2007)
OBJECTIVE: The incidence of childhood obesity and type 2 diabetes has reached epidemic proportions. Glucocorticoid excess causes central obesity and diabetes mellitus as seen in Cushing's syndrome. The 11beta-hydroxysteroid dehydrogenase type 1 enzyme (11beta-HSD1) regenerates active cortisol from inactive cortisone. Altered 11beta-HSD1 may cause tissue-specific Cushing's syndrome with central obesity and impaired glucose homeostasis. DESIGN, PATIENTS, AND METHODS: Clinical and laboratory characteristics, and anthropometric measurements were determined in 15 male and 6 female obese pubertal children (aged 12-18 years, Tanner stages 2-5). In addition, analyses of 24-h excretion rates of glucocorticoids were also performed in 21 age-, sex-, and pubertal stage-matched non-obese children using gas chromatographic-mass spectrometric (GC-MS) analysis. RESULTS: 11beta-HSD1 activity (urinary tetrahydrocortisol (THF) + 5alpha-THF/tetrahydrocortisone (THE) ratio) was lower in obese when compared with non-obese boys. In addition, obese children had a higher total cortisol metabolite excretion than non-obese children. 11beta-HSD1 activity was significantly related to age in lean and obese children. Standard deviation score (SDS)-body mass index did not correlate with 11beta-HSD1 activity, or with total cortisol metabolite excretion within each group. In obese children, 11beta-HSD1 activity and total cortisol metabolite excretion showed no correlation to waist-to-hip ratio, fat mass (percentage of body mass), or the homeostasis model assessment of insulin resistance index. CONCLUSIONS: In conclusion, our findings strongly suggest that 11beta-HSD1 activity increases with age, and is reduced in obese boys. In addition, obese children have a higher total cortisol metabolites excretion suggesting a stimulated hypothalamus-pituitary-adrenal axis.